2019
DOI: 10.1002/hbm.24538
|View full text |Cite
|
Sign up to set email alerts
|

Cortical pattern of reduced perfusion in hearing loss revealed by ASL‐MRI

Abstract: Age‐related hearing loss (HL) can be related to brain dysfunction or structural damage and may result in cerebral metabolic/perfusion abnormalities. Arterial spin labeling (ASL) magnetic resonance imaging (MRI) allows investigating noninvasively brain perfusion changes. Pseudocontinuous ASL and T1‐weighted MRI (at 3 T) and neuropsychological testing (Montreal Cognitive Assessment) were performed in 31 HL (age range = 47–77 years, mean age ± SD = 63.4 ± 8.4 years, pure‐tone average [PTA] HL > 50 dB) and 28 norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 66 publications
(84 reference statements)
0
15
0
Order By: Relevance
“… Windsor and Ruckenstein (2018) , in fact suggested that anti-inflammatory therapies may reduce sensorineural hearing loss. In addition, a study by Ponticorvo et al (2019) showed that there was reduced cerebral perfusion in patients with hearing loss detectable prior to brain structural damage. This is not to deny that the disconnection from the auditory environment that hearing deficit implies may also play a role in inducing cognitive deficit, since those using hearing aids reduce their risk for cognitive decline ( Amieva et al, 2018 ; Maharani et al, 2018 ), but hearing deficit may fit into the hypothesis presented here better than suspected.…”
Section: Discussionmentioning
confidence: 99%
“… Windsor and Ruckenstein (2018) , in fact suggested that anti-inflammatory therapies may reduce sensorineural hearing loss. In addition, a study by Ponticorvo et al (2019) showed that there was reduced cerebral perfusion in patients with hearing loss detectable prior to brain structural damage. This is not to deny that the disconnection from the auditory environment that hearing deficit implies may also play a role in inducing cognitive deficit, since those using hearing aids reduce their risk for cognitive decline ( Amieva et al, 2018 ; Maharani et al, 2018 ), but hearing deficit may fit into the hypothesis presented here better than suspected.…”
Section: Discussionmentioning
confidence: 99%
“…This The arterial spin labelling magnetic resonance imaging, instead, analyses cerebral perfusion in vivo and allows non-invasive investigation of brain perfusion changes. This technique revealed that perfusion within the bilateral primary auditory cortex in patients with hearing impairment is reduced, especially in the right lateral Heschl's gyrus, a critical area for auditory processing and which is also involved in many other cognitive skills [44].…”
Section: Changes In Brain Structure and Functionmentioning
confidence: 99%
“…Usually, HL seems to speed up cognitive decline through the combination of social and sensory isolation and through an increased cognitive load 13 . Indeed, peripheral HL decreases local cerebral blood flow in primary auditory cortex 14 and it is associated with decreased volumes in the auditory cortex, temporal lobe and whole brain, and also with a functional reorganization of the auditory cortical networks, consistent with more demanding listening and a reduction of cognitive reserve 13 . Furthermore, a reduction of perfusion in primary auditory cortex has been found by ASL-MRI in patients affected by HL in the early stages, suggesting that there is a relationship between HL and cortical activation/metabolism, even if no atrophy was found 14 .…”
Section: Introductionmentioning
confidence: 99%